Forms of Corporate Social Responsibility Practices of Companies in Malaysia - Neoh, Sher Lyn (2015)
This management project seeks to explore the corporate social responsibility (CSR) practices of companies in Malaysia. To do this, the first part of the study looks into the general views of CSR along with its drivers and enablers before going into the collaboration patterns and drivers of companies and non-governmental organisation. In addition, some findings of multi-national corporations and CSR in Malaysia is also brought forward in this study. The companies selected for this study will then be rated based on the four focus areas by Bursa, which are Community, Environment, Marketplace, and Workplace. The findings will then be used for discovering the patterns of each company groups and their CSR practices.